Pemikiran Waleed el-Ansary tentang â€œA Common Wordâ€ dalam Perspektif Metafisika Perennial - Ja?far, Suhermanto (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2012)
The discourse of ?the Common Word? between us and you have initiated a series of seminars involving world religious institutions. Theological implications of common word become prevalent discussion. Fundamental questions that arise are: ?When both Islam and Christianity claim to have received the revelation of God, then what does that mean that the word of God has become a book? Or transformed into the image of Jesus? ?However, it does not mean that such matters can simply be brought into the realm of theological studies, because it will lead to a polemic and highlight the differences rather than the pure spirit of faith. Theology will only hold us to understand the main doctrines that had been circling around each religious tradition. Therefore, this article, that explores the idea of Waleed el-Ansary, is presented as an effort to understand the ?Word of God? within Islam?s and Christianity?s perspective, so as religious people, we all get the meaningfulness of life or even salvation.